2009
DOI: 10.1179/026708408x370203
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on phosphorus doping using H3PO4 as doping source by simple dip method and its electrical characterisation

Abstract: In this article, the authors present the work on emitter diffusion in crystalline silicon solar cell fabrication, and determine that phosphorus doping using phosphoric acid (H 3 PO 4 ) with dipping is convenient and cost effective. H 3 PO 4 was mixed with different solvents such as deionised water, ethanol, methanol and butanol. However, deionised water is hydrophobic to the silicon surface. The emitter layers were obtained by varying emulsion concentrations and diffusion temperatures. The sheet resistance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Therefore, in the interest of environmentfriendliness as well as inexpensive manufacturing, use of phosphoric acid (H 3 PO 4 ) as the dopant source represents an almost perfect alternative. Several approaches of phosphorus diffusion have been reported including spin-on (Ahmad et al 2017;Balaji et al 2015;Moon et al 2009), ion implantation (Lee et al 2013;Yang et al 2015), and spray-on phosphoric acid (Basu et al 2016). In most of the reported work, use of commercially-manufactured dopants increases costs and places constraints on its shelf-life.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in the interest of environmentfriendliness as well as inexpensive manufacturing, use of phosphoric acid (H 3 PO 4 ) as the dopant source represents an almost perfect alternative. Several approaches of phosphorus diffusion have been reported including spin-on (Ahmad et al 2017;Balaji et al 2015;Moon et al 2009), ion implantation (Lee et al 2013;Yang et al 2015), and spray-on phosphoric acid (Basu et al 2016). In most of the reported work, use of commercially-manufactured dopants increases costs and places constraints on its shelf-life.…”
Section: Methodsmentioning
confidence: 99%
“…These experiments were based on controlled variations in concentrations of H 3 PO 4 four different diffusion temperatures. Moon et al (2009) reported that H 3 PO 4 diluted with deionized (DI) water exhibit non-uniformity over the silicon wafer due to poor surface wettability. This issue was resolved using radio corporation of America (RCA), RCA-2 standard solution to form hydrated surfaces (Ahmad et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [ 12 ] presents work using phosphoric acid dissolved in different organic solvents as well as deionized water. However, deionized water resulted in the silicon surface being hydrophobic.…”
Section: Introductionmentioning
confidence: 99%